2016
DOI: 10.1111/jcpp.12620
|View full text |Cite
|
Sign up to set email alerts
|

Defining ADHD symptom persistence in adulthood: optimizing sensitivity and specificity

Abstract: Objective Longitudinal studies of children diagnosed with ADHD report widely ranging ADHD persistence rates in adulthood (5-75%). This study documents how information source (parent vs. self report), method (rating scale vs. interview), and symptom threshold (DSM vs. norm-based) influence reported ADHD persistence rates in adulthood. Method 579 children were diagnosed with DSM-IV ADHD-Combined Type at baseline (ages 7.0-9.9 years) and 289 classmates served as a local normative comparison group (LNCG), 476 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
143
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(150 citation statements)
references
References 20 publications
4
143
1
2
Order By: Relevance
“…One study evaluated how differences in case definition might impact persistence estimates in the 16-year clinical follow-up of the Multimodal Treatment Study of ADHD (MTA) [27•]. Persistence estimates varied widely from 1.9 % (requiring DSM-IV criteria, combining parent and self-report in the Diagnostic Interview Schedule for Children (DISC) with an item-level AND rule) to 61.4 % (requiring norm-based symptom count, combining parent and self-report in the DISC with an item-level OR rule).…”
Section: Conceptual and Methodological Issues Inherent To The Study Omentioning
confidence: 99%
“…One study evaluated how differences in case definition might impact persistence estimates in the 16-year clinical follow-up of the Multimodal Treatment Study of ADHD (MTA) [27•]. Persistence estimates varied widely from 1.9 % (requiring DSM-IV criteria, combining parent and self-report in the Diagnostic Interview Schedule for Children (DISC) with an item-level AND rule) to 61.4 % (requiring norm-based symptom count, combining parent and self-report in the DISC with an item-level OR rule).…”
Section: Conceptual and Methodological Issues Inherent To The Study Omentioning
confidence: 99%
“…Symptoms tend to attenuate with age, although around 60% of individuals have symptom persistence into adulthood and 40% show both symptom persistence and impairment (Sibley, Swanson et al., 2017). Adult ADHD has been assumed to be a continuation of childhood ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…Using parent reports and self-reports of symptoms and impairment on rating scales and structured interviews from MTA, Sibley et al (2017) found that when using combined parent reports and selfreports, the balance between diagnostic sensitivity and specificity was optimized by a rating scale method and a norm-based symptom threshold (i.e., four symptoms of either IN or HI). The findings suggest that a thorough assessment of ADHD in adulthood should ideally include reports by other informants and self-ratings.…”
Section: Adhd Persistence Rates In Adulthoodmentioning
confidence: 99%
“…The occurrence and prediction of developmental trajectories of persisting and remitting ADHD, as well as late-onset ADHD, are very hot topics in the field of ADHD, and thorough assessments of ADHD in adulthood will be crucial for the field to move forward. Sibley et al (2017) reported that the persistence of ADHD in young adulthood was approximately 60%, and 41.1% of the ADHD group met both the optimized persistence criteria and presence of impairment. This adds to the ongoing and somewhat polarized debate, where ADHD on one hand is conceptualized as a condition that children will eventually outgrow, and on the other hand, as a chronic neurodevelopmental disorder that does not change with development.…”
Section: Adhd Persistence Rates In Adulthoodmentioning
confidence: 99%
See 1 more Smart Citation